Stability of magnetopause boundary and generation of long period geomagnetic pulsations - Mishra S.P.; Misra K.D.; Singh R.N. (My University, 2025)
The effect of irrotational electric field and tensorial plasma conductivity on the growth rate of Kelvin-Helmholtz instability has been investigated. It is shown that the presence of irrotational electric field alters the growth rate. The dependence of Pedersen conductivity on the growth rate has been shown. The Kelvin-Helmholtz perturbations generate a surface wave in the frozen-in plasma. The propagation of these waves gives rise to polarization of the transverse hydromagnetic pulsations. It is shown that the modified K-H spectrum would result in a corresponding change in polarization features of the hydromagnetic pulsations. © 1975 the Indian Academy of Sciences.